Metabolic features of cancer cells impact immunosurveillance. Issue 6 (23rd June 2021) - Joseph, Adrien; Juncheng, Pan; Mondini, Michele; Labaied, Nizar; Loi, Mauro; Adam, Julien; Lafarge, Antoine; Astesana, Valentina; Obrist, Florine; Klein, Christophe; Bloy, Norma; Stoll, Gautier; et al.
Abstract : Background: Tumors rewire their metabolism to achieve robust anabolism and resistance against therapeutic interventions like cisplatin treatment. For example, a prolonged exposure to cisplatin causes downregulation of pyridoxal kinase (PDXK), the enzyme that generates the active vitamin B6, and upregulation of poly ADP-ribose (PAR) polymerase-1 (PARP1) activity that requires a supply of nicotinamide (vitamin B3) adenine dinucleotide. We investigated the impact of the levels of PDXK and PAR on the local immunosurveillance (ie, density of the antigen presenting cells and adaptive immune response by CD8 T lymphocytes) in two different tumor types. Methods: Tumors from patients with locally advanced cervical carcinoma (LACC) and non-small cell lung cancer (NSCLC) were stained for PAR, PDXK, dendritic cell lysosomal associated membrane glycoprotein (DC-LAMP) and CD8 T cell infiltration. Their correlations and prognostic impact were assessed. Cisplatin-resistant NSCLC cell clones isolated from Lewis-lung cancer (LLC) cells were evaluated for PAR levels by immunoblot. Parental (PAR low ) and cisplatin-resistant (PAR high ) clones were subcutaneously injected into the flank of C57BL/6 mice. Tumors were harvested to evaluate their immune infiltration by flow cytometry. Results: The infiltration of tumors by CD8 T and DC-LAMP + cells was associated with a favorable overall survival in patients with LACC (p=0.006 and p=0.008, respectively) and NSCLC (p<0.001 for both CD8 T and DC-LAMP cells). We observed a positive correlation between PDXK expression and the infiltration by DC-LAMP (R=0.44, p=0.02 in LACC, R=0.14, p=0.057 in NSCLC), and a negative correlation between PAR levels and CD8 T lymphocytes (R=−0.39, p=0.034 in LACC, R=−0.18, p=0.017 in NSCLC). PARP1 is constitutively hyperactivated in cisplatin-resistant LLC cells manifesting elevated intracellular levels of poly(ADP-ribosyl)ated proteins (PAR high ). Tumors formed by such cancer cells injected into immunocompetent mice were scarcely infiltrated by CD8 T (p=0.028) and antigen presenting cells (p=0.086). Conclusions: Oncometabolic features can impact local immunosurveillance, providing new functional links between cisplatin resistance and therapeutic failure.